From Text to Context: The Role of Kyai in Shaping Modern Islamic Inheritance Law - Nur, Muhammad; Nisa, Siti Maymanatun; Arhamzah, Tashdieq Ulil Amri; Sidqi, Imaro; Witro, Doli (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
This study aims to analyse the reasons for applying modern Islamic inheritance law based on the ijtihad of Kyai and examine the construction of modern Islamic inheritance law developed in Kajen District. This study is an empirical legal study using a sociological approach to law. Data was obtained through in-depth interviews with Kyai, participatory observation, documentary studies, and Focus Group Discussions (FGD). This study shows that the development of modern Islamic inheritance law in the Muslim community of Kajen District is influenced by changes in mindset, attitudes, and social culture. Kyai has developed a legal construction of inheritance that combines local cultural values with contemporary Islamic principles through philosophical, juridical, and socio-cultural arguments. The three main provisions resulting from this ijtihad include: first, the expansion of the concept of substitute heirs, not limited to grandchildren but also including siblings and parents, even when the testator is still alive; second, equality in the distribution of inheritance between men and women; and third, the recognition of the right to maintenance and mandatory bequests for children born out of wedlock through the mechanism of substitute heirs. This research contributes academically by demonstrating that local traditions play a strategic role in shaping the pattern of Islamic inheritance law, ijtihad, thereby enriching the contemporary sociology of Islamic law.